Follicular fluid extracellular vesicles improve bovine oocyte quality via lipid and mitochondrial modulation - Schneberger, Fernanda; Bridi, Alessandra; Ferraz, Priscila Assis; de Oliveira, José Roberto Quirino; Munhoz, Lorena Calixto; Sangalli, Juliano Rodrigues; Prado, Cibele Maria; Janini, Ludimila Cardoso Zoccal; Perecin, Felipe; da Silveira, Juliano Coelho; Leal, Cláudia Lima Verde (Frontiers in Veterinary Science, 2026)
In vitro maturation (IVM) systems remain sub-optimal, compromising oocyte cytoplasmic competence and subsequent embryo quality by failing to reproduce follicular fluid (FF) microenvironment communication, specifically by lacking extracellular vesicles (ffEVs). In order to determine the contribution of ffEVs on oocyte maturation and quality, oocytes were assessed for nuclear maturation, mitochondrial activity, reactive oxygen species (ROS) levels, and lipid metabolism parameters such as lipid droplet (LD) area, HSL phosphorylation and glycerol release levels, after IVM of COC with or without ffEVs. Subsequent embryo development rates and blastocyst quality (total cell number, mitochondrial activity and LD area) were also evaluated. Additionally, the relative abundance of mRNA and miRNAs that regulate lipid metabolism as well as transcripts of antioxidant enzymes were also analyzed in oocytes, cumulus cells (CC), and ffEVs. While nuclear maturation was unaffected, ffEVs supplementation significantly improved cytoplasmic competence, evidenced by increased mitochondrial activity and lower ROS levels. Despite lipolytic activity being unchanged, the oocyte LD area increased implying enhanced lipogenesis and/or lipid uptake independent of lipolytic activity. These effects did not alter early embryonic development rates and total cell number in Day 7 blastocysts. Nonetheless, blastocyst mitochondrial activity and LD area reduced, indicating that energy and lipid metabolism are being modulated in a beneficial way, favoring embryonic quality. Although many candidates lipid-regulating miRNAs and mRNAs, as well as antioxidant enzyme mRNAs, were detected in ffEVs, their expression in oocytes and CC was unchanged after IVM. Only bta-miR-23b-3p was downregulated in CC. In conclusion, ffEVs induce favorable metabolic alterations in the oocyte, increasing oocyte quality and improving blastocyst lipid contents. This shows ffEVs as a promising additive tool to enhance IVM condition in bovine embryo IVP systems.